Early Childhood Development : A Review of the Global Evidence - Nadeau, Sophie (World Bank, Washington, DC, 2016)
Early Childhood Development (ECD) is a holistic concept that refers to the physical, cognitive, socio-emotional, and linguistic development of young children until the time they transition to primary school. This policy brief highlights that developmental gaps in the early years of a child’s life do not narrow by themselves over time, are likely to be particularly severe for children born to teenage mothers, and lead to costly consequences for individuals, families, and societies. In turn, this policy brief also documents that strong evidence exist on the significant benefits that quality ECD interventions yield in both the short and longer terms. Different types of ECD interventions are most relevant and are complementary at different times of a child’s development. For example, interventions to promote infant and child health and to reduce malnutrition are most effective in the 1,000-day window from pregnancy to a child’s second birthday, and programs that enhance both early stimulation and nutrition are more likely to generate long-lasting impacts than nutrition alone. Strong evidence also exists on the positive impacts of high quality center-based programs for young children (i.e. daycares and preschools), including in low and middle-income countries, and these types of programs can also generate positive impacts for other family members, including caregivers and siblings. Finally, providing cash transfers to families can be an effective way to enhance the ECD outcomes of the poorest children, especially when combined with specific health, nutrition, and early stimulation interventions. In sum, this policy brief provides an overview of why early childhood is a critical period of human development and of the several types of ECD interventions that have been proven effective to improve children’s development and life-long prospects.